PENGARUH PENGGUNAAN AMPAS TAHU SEBAGAI MAKANAN IKAN LELE DI DESA SOROMA’ASI KECAMATAN ONOHAZUMBA - Waruwu, Liswati (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2024)
This research was carried out because there were no people who used tofu dregs as food for catfish, so the people in Soroma'asi village cultivated catfish for their own family needs and not to sell in the market. This research aims to determine the effect of using tofu dregs as food for catfish in Soroma'asi Village, Onohazumba District. This type of research is quantitative with a pure experimental method (True Experiment), with a completely randomized design (RAL). The population of this study was 20 catfish and the research sample was catfish with five treatments and four replications. The treatments applied were P0 (bran giving), P1 (25 grams), P2 (50 grams), P3 (75 grams), and P4 (100 grams). This research data was analyzed using the Kolmogorov-Smirnov test for normality test, homogeneity test, hypothesis test using the SPSS (Statistical Product and Service Solution) application. The results of this research are known to be Fcount 3.442 and asymp 0.035. When compared with 0.035 then Fcount 3.442 > Ftable 2.87. Furthermore, the asymp value is 0.035 < 0.05. This means that the use of tofu dregs as food for catfish in Soroma'asi Village, Onohazumba District has an effect on the growth of catfish, so that Ha is accepted (there is an influence of using tofu dregs as food for catfish in Soroma'asi Village, Onohazumba District) and H0 is rejected. It is hoped that this research can provide information to the public, especially fish farmers, to make more use of tofu dregs as food for catfish.